2001
DOI: 10.4049/jimmunol.166.4.2750
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Th1 Chemokine IFN-γ-Inducible Protein 10 in the Airway Alters Mucosal Allergic Sensitization in Mice

Abstract: Although the preliminary characterization of chemokines and their receptors has been prolific, comparatively little is known about the role of chemokines in the evolution of immune responses. We speculate that the preferential recruitment of a particular immune cell population has implications for the short- and long-term features of an adaptive response. To test this hypothesis, we employed adenovirus-mediated gene transfer to express the Th1-affiliated, CXC chemokine IFN-γ-inducible protein (IP) 10 in the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…In addition, adenoviral overexpression of CXCL10 during sensitization to OVA decreased eosinophil accumulation and IL-4 levels after OVA challenge (33). However, CXCL10 transgenic mice displayed increased eosinophil accumulation, airway hyperreactivity, and IL-4 levels after OVA challenge (48).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, adenoviral overexpression of CXCL10 during sensitization to OVA decreased eosinophil accumulation and IL-4 levels after OVA challenge (33). However, CXCL10 transgenic mice displayed increased eosinophil accumulation, airway hyperreactivity, and IL-4 levels after OVA challenge (48).…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that asthmatics have increased levels of CXCL10 in their bronchoalveolar lavage (BAL) 3 fluid (32). Overexpression of CXCL10 during sensitization to OVA has been shown to decrease levels of Th2-type cytokines and eosinophil accumulation in the airway after OVA challenge (33). CXCL10 has also been demonstrated to enhance pulmonary eosinophil accumulation and increase pulmonary levels of Th2 type cytokines after cockroach allergen challenge (34).…”
mentioning
confidence: 99%
“…Whether CXCL9 and CXCL10 enhance or dampen allergic inflammation may depend on the location and timing of their production. For example, in a mouse model, targeted overexpression of CXCL10 to the lung inhibited the development of Ag-induced airway eosinophilia (41). The authors suggested that this was most likely due to recruitment of Th1-type cells that shifted the balance away from a Th2 response.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of (27,29). In addition, the observation that introduction of exogenous IFN-␥ into the airway can initially down-regulate the Th2-induced response may suggest that IP10 can have an immunomodulatory role during allergic responses (23,26).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether IFN-␥ acts directly or indirectly by altering local and/or systemic inflammatory immune responses. Recently, it has been shown that overexpression of IP10 during sensitization to OVA decreased levels of IL-4 and eosinophil accumulation in the airway following OVA challenge (29). To further investigate the role of IP10 in the allergic response, the effect of neutralization of IP10 at the time of allergen challenge was investigated in these studies.…”
mentioning
confidence: 99%